Breaching-point. (Economist, 2016)
The article discusses incentives to improve Internet and cyber security, including in regard to the diminishing of high technology firms' reputation caused by computer hacking. An overview of the security risks concerning the Internet of things (IOT), including the inability of IOT devices to have their computer software updated and secured, is provided.